Bipedal Steps in the Development of Rhythmic Behavior in Humans. (16th December 2019) - Larsson, Matz; Richter, Joachim; Ravignani, Andrea
We contrast two related hypotheses of the evolution of dance:H1 : Maternal bipedal walking influenced the fetal experience of sound and associated movement patterns;H2 : The human transition to bipedal gait produced more isochronous/predictable locomotion sound resulting in early music-like behavior associated with the acoustic advantages conferred by moving bipedally in pace. The cadence of walking is around 120 beats per minute, similar to the tempo of dance and music. Human walking displays long-term constancies. Dyads often subconsciously synchronize steps. The major amplitude component of the step is a distinctly produced beat. Human locomotion influences, and interacts with, emotions, and passive listening to music activates brain motor areas. Across dance-genres the footwork is most often performed in time to the musical beat. Brain development is largely shaped by early sensory experience, with hearing developed from week 18 of gestation. Newborns reacts to sounds, melodies, and rhythmic poems to which they have been exposed in utero . If the sound and vibrations produced by footfalls of a walking mother are transmitted to the fetus in coordination with the cadence of the motion, a connection between isochronous sound and rhythmical movement may be developed. Rhythmical sounds of the human mother locomotion differ substantially from that of nonhuman primates, while the maternal heartbeat heard is likely to have a similar isochronous character across primates, suggesting a relatively more influential role of footfall in the development of rhythmic/musical abilities in humans. Associations of gait, music, and dance are numerous. The apparent absence of musical and rhythmic abilities in nonhuman primates, which display little bipedal locomotion, corroborates that bipedal gait may be linked to the development of rhythmic abilities in humans. Bipedal stimuli in utero may primarily boost the ontogenetic development. The acoustical advantage hypothesis proposes a mechanism in the phylogenetic development.